2009
DOI: 10.1111/j.1365-2214.2009.00973.x
|View full text |Cite
|
Sign up to set email alerts
|

‘I felt I have grown up as an adult’: caregiving experience of children affected by HIV/AIDS in China

Abstract: While the increased caregiving responsibilities among children reflected some cultural beliefs and had some positive effect on personal growth, the caregiving experience generally negatively effected the children's physical and mental health and schooling. The findings in the current study suggest that community-based caregiving support is necessary in areas with high prevalence of HIV and limited resources, especially for the families lacking adult caregivers. In addition, social and psychological support sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Although child gender was not reported to play a role in children’s education in our study, our findings support the review article in that mothers in our study also mentioned that their living arrangement and poverty were barriers to their children attending school. Children from families living with HIV in Haiti and elsewhere often also face psychosocial stressors related to HIV/AIDS stigma from community members and increased responsibilities in housework and caring for self, younger siblings and parents with illness (Ji et al, 2007; Skovdal, Ogutu, Aoro, & Campbell, 2009; Xu, Wu, Duan, Han, & Rou, 2010; Zhang et al, 2009). Among the children who were able to attend school in our study, the psychosocial stressors they experienced influenced their behaviors and school performance.…”
Section: Discussionmentioning
confidence: 99%
“…Although child gender was not reported to play a role in children’s education in our study, our findings support the review article in that mothers in our study also mentioned that their living arrangement and poverty were barriers to their children attending school. Children from families living with HIV in Haiti and elsewhere often also face psychosocial stressors related to HIV/AIDS stigma from community members and increased responsibilities in housework and caring for self, younger siblings and parents with illness (Ji et al, 2007; Skovdal, Ogutu, Aoro, & Campbell, 2009; Xu, Wu, Duan, Han, & Rou, 2010; Zhang et al, 2009). Among the children who were able to attend school in our study, the psychosocial stressors they experienced influenced their behaviors and school performance.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the measures/scales in the inventory were culturally adapted from existing measures in literature through qualitative studies (Zhang et al, 2009; Zhao et al, 2007; Zhao, Li, Kaljee, Zhang, et al, 2009). During the survey, clarification and/or instruction were provided promptly when needed.…”
Section: Methodsmentioning
confidence: 99%
“…These physical and emotional demands may comprised the parenting quality, disrupted family routines (Murphy & Marelich, 2008). Children may be required to take the adult responsibility to provide care to ill adults, perform household work, taking care of younger siblings (Zhang et al, 2009) or even become the breadwinners in the family. These can increase the children's risk to poor health, school drop-out, and child labor (Xu, Wu, Duan, Han, & Rou, 2010).…”
Section: Impact Of Parental Hivmentioning
confidence: 99%
“…Self-esteem, self-confidence, and coping self-efficacy were associated with increased resilience in a study conducted in Africa (Betancourt et al, 2011). Worldwide studies suggested that caregiving responsibilities among children affected by HIV may have some positive effect on personal growth and contribute to a child's positive competence in supporting their households (Campbell et al, 2012; Skovdal, 2010; Zhang et al, 2009). …”
Section: Resilience Processmentioning
confidence: 99%